Evaluating social protective factors for violence involvement in Honduras. Issue 1 (2nd January 2020) - Hare, Tom; Miller-Graff, Laura E.; Guzman, Juan Carlos
ABSTRACT: Endemic levels of violence continue to stall social and economic development in Honduras. Significant emphasis has been placed on social protective factors such as resilience and cohesion in violence prevention policies and programmes. This article evaluates these factors using previously validated tools applied to over 1, 200 non-incarcerated and incarcerated individuals. Results demonstrate that resilience and cohesion are not as strongly associated with violence involvement in these samples as hypothesised, while early behaviour problems have a greater association with current violence involvement. These results suggest the need for further investigation into critical violence prevention hypotheses.